(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The Gongola Sub-Basin plays a significant role in understanding the geologic evolution of the Upper Benue Trough, it is equally important due to hydrocarbon exploration ongoing in the Sub-Basin. Palynological and lithological analyses were conducted on studied samples to interpret paleoenvironmental conditions of the sedimentary deposit. Palynological evidence including relative abundance and diversity of miospores, marine (dinocysts) and freshwater (Pediastrum and Botryococcus) indices coupled with lithological data recorded from twelve (12) boreholes, each drilled to the depth of 63 meters have been used to interpret the paleoenvironment of the Upper Cretaceous and Tertiary sedinentary deposits of the Kashere-Billiri-Futuk general area within the Gongola Sub-Basin, Upper Benue Trough in northeast Nigeria. The admixture of palynomorphs recovered from borehole sections D, F, I, N, O, R, S, T, V and X which include Proxapertites cursus, Proxapertites operculatus (brackish water palynomorphs), Cingulatisporites ornatus, Gleicheniidites sp., Cyathidites australis, Longapertites marginatus, Echitriporites trianguliformis, Proxapertites operculatus, Distaverrusporites simplex and Diatom frustules revealed a primarily terrestrial deposition environment characterized by lacustrine settings . Borehole sections B and P with characteristic palynoflora of Cingulatisporites ornatus, Tricolporopollenites sp., Gleicheniidites senonicus, Ephedripites sp. Cyathidites sp., Longapertites sp., Echitriporites trianguliformis and Distaverrusporites simplex, however, indicates a deposition of sediments with a predominantly fluvial-lacustrine influences.